Artificial Intelligence and Digital Tafsīr: Assessing the Interpretive Accuracy of ChatGPT’s Engagement with Tafsīr al-Qurṭūbī - Fasyani, M. Faidh; Abdul Muqsid; Abdal Wahab Mujtaba (Faculty of Ushuluddin and Philosophy, Sunan Ampel State Islamic University Surabaya, 2024)
T he increasing use of artificial intelligence (AI) in Qur’anic studies has raised concerns about the reliability and epistemic authority of interpretations generated by AI. This study examines the issue of interpretive accuracy by evaluating how ChatGPT responds when explicitly asked to interpret verses based on Taf sīr al-Qurṭūbī . This study focuses on Surah al-Mā’idah [5]: 106–108, which discusses legal testimony, a theme rich in fiqh details. This study aims to assess whether ChatGPT accurately reflects al-Qurṭūbī’s exegetical thought or merely produces a general summary. Using qualitative methods, including literature review and comparative text analysis, ChatGPT’s responses were systematically compared with the original Arabic text of al-Qurṭūbī’s tafsīr . The results reveal significant gaps: ChatGPT frequently overlooks crucial legal arguments, misrepresents theological nuances, and fails to reproduce the distinctive interpretive structure of classical tafsīr . These limitations stem from the model’s inability to access verified exegesis corpora and its inadequate contextual understanding. Nevertheless, this study acknowledges the potential of ChatGPT in an educational context and provides accurate sources and ethical guidelines to support it. The research concludes that AI can assist in interpreting the Qur’an in a digital context, but it should not replace traditional scholarly authority.